Health Promotion Quality Regarding Post-Placental IUDs in Malang Regency - Henri Sulistiyanto; Soetrisno; Ahmad Arman Subiyanto; Retno Setyowati (Asian Journal of Health Research, 2024)
Introduction: Community welfare is confronted with a substantial challenge by Indonesia's burgeoning population, and the government's principal aim is the promotion of Long-acting reversible contraceptives (LARC). Post-placental IUD is an efficacious method that incorporates health promotion by means of midwife-delivered contraceptive counseling. Counseling promotes the development of positive relationships, knowledge, attitudes, and behaviors, thereby fostering responsible behavior and individual agency in decision-making. Nevertheless, the low utilization rate of postpartum IUD contraception can be attributed to the scarcity of information regarding the mother. The objective of this study is to examine the level of health promotion regarding post-placental IUD family planning in Malang Regency. Material and Methods: Descriptive methods will be employed, including verbal and written observations of behavior and descriptive data on individuals. The interview-based data collection process spanned the months of June to August 2023. Results: The research results suggest that inadequate efforts to promote postpartum IUD contraception are due to a dearth of understanding, motivation, resources, geographical proximity, and community customs. The objective is to improve the existing insufficiency of post-placental IUD family planning promotion in Malang Regency. Conclusion: From the beginning of pregnancy onwards, expectant women must be consistently motivated and educated about health promotion and family planning in order to develop an interest in and understanding of the choice of post-placental IUD family planning.